Bacteriocins, Antimicrobial Peptides from Bacterial Origin: Overview of Their Biology and Their Impact against Multidrug-Resistant Bacteria - Alexis Simons; Kamel Alhanout; Raphaël E. Duval (Microorganisms, 2020)
Currently, the emergence and ongoing dissemination of antimicrobial resistance among bacteria are critical health and economic issue, leading to increased rates of morbidity and mortality related to bacterial infections. Research and development for new antimicrobial agents is currently needed to overcome this problem. Among the different approaches studied, bacteriocins seem to be a promising possibility. These molecules are peptides naturally synthesized by ribosomes, produced by both Gram-positive bacteria (GPB) and Gram-negative bacteria (GNB), which will allow these bacteriocin producers to survive in highly competitive polymicrobial environment. Bacteriocins exhibit antimicrobial activity with variable spectrum depending on the peptide, which may target several bacteria. Already used in some areas such as agro-food, bacteriocins may be considered as interesting candidates for further development as antimicrobial agents used in health contexts, particularly considering the issue of antimicrobial resistance. The aim of this review is to present an updated global report on the biology of bacteriocins produced by GPB and GNB, as well as their antibacterial activity against relevant bacterial pathogens, and especially against multidrug-resistant bacteria.